Characterizing groundwater flow and heat transport in fractured rock using fiber‐optic distributed temperature sensing. Issue 10 (23rd May 2013) - Read, T.; Bour, O.; Bense, V.; Le Borgne, T.; Goderniaux, P.; Klepikova, M.V.; Hochreutener, R.; Lavenant, N.; Boschero, V.
Abstract : [1] We show how fully distributed space‐time measurements with Fiber‐Optic Distributed Temperature Sensing (FO‐DTS) can be used to investigate groundwater flow and heat transport in fractured media. Heat injection experiments are combined with temperature measurements along fiber‐optic cables installed in boreholes. Thermal dilution tests are shown to enable detection of cross‐flowing fractures and quantification of the cross flow rate. A cross borehole thermal tracer test is then analyzed to identify fracture zones that are in hydraulic connection between boreholes and to estimate spatially distributed temperature breakthrough in each fracture zone. This provides a significant improvement compared to classical tracer tests, for which concentration data are usually integrated over the whole abstraction borehole. However, despite providing some complementary results, we find that the main contributive fracture for heat transport is different to that for a solute tracer. Key Points: FO‐DTS detects fracture flows of ≅4 L min −1 Temperature response of fracture zones calculated for thermal tracer test Most significant fracture for solute transport not the most significant for heat